2020
DOI: 10.1371/journal.pone.0233166
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hypertension, hyperglycemia and dyslipidemia from retinal fundus photographs via deep learning: A cross-sectional study of chronic diseases in central China

Abstract: Retinal fundus photography provides a non-invasive approach for identifying early microcirculatory alterations of chronic diseases prior to the onset of overt clinical complications. Here, we developed neural network models to predict hypertension, hyperglycemia, dyslipidemia, and a range of risk factors from retinal fundus images obtained from a cross-sectional study of chronic diseases in rural areas of Xinxiang County, Henan, in central China. 1222 high-quality retinal images and over 50 measurements of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 36 publications
1
62
0
Order By: Relevance
“…Additionally, other risk factors such as age, drinking status, smoking status, salty taste, and body mass index (BMI) were also predicted with accuracies > 70%. These results support the application of deep learning to retinal fundus images in the identification of individuals at risk for CVD [ 30 ].…”
Section: Heart Eye and Aisupporting
confidence: 77%
See 1 more Smart Citation
“…Additionally, other risk factors such as age, drinking status, smoking status, salty taste, and body mass index (BMI) were also predicted with accuracies > 70%. These results support the application of deep learning to retinal fundus images in the identification of individuals at risk for CVD [ 30 ].…”
Section: Heart Eye and Aisupporting
confidence: 77%
“…The use of deep learning combined with retinal imaging in the diagnosis of cardiovascular conditions is a relatively new area of research (Table 1 [23][24][25][26][27][28][29][30][31]). In 2007, researchers from Australia, Singapore, and the USA showed that retinopathies obtained from fundus photographs were associated with the presence of any degree of coronary artery calcification (CAC) score > 0, measured by cardiac computed tomography scanning (odds ratio (OR): 1.22; 95% CI: 1.04 -1.43) in a multi-ethnic population without clinical heart disease, after adjustment for multiple variables [23].…”
Section: Retinal Imaging Heart Disease and Deep Learningmentioning
confidence: 99%
“…The retinal vasculature features used in the p r e d i c t i o n m o d e l s s h o w e d c o n s i d e r a b l e discrimination. With the assistance of deep learning, retinal images have recently been assessed for corresponding changes under the condition of hypertension 15) , hyperglycemia, and dyslipidemia 16) . Retinal imaging was also considered a potential biomarker in the assessment of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal vasculature holds sufficient information regarding vascular health [7][8][9][10] , heart failure 11) , hypertension 12) , and subtypes of stroke 13) . With the assistance of deep learning, recent studies have explored the value of retinal imaging in the prediction of cardiovascular risk factors 14) , as well as the changes of retinal microvasculature affected by hypertension 15) and other chronic diseases 16) . Besides, retinal vasculature was found to be associated with CAD, which could provide additional implications on cardiovascular risks coexisting with microvascular dysfunction in patients 17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…6 More recently, several studies on deep learning-predicted systemic conditions from retinal photographs have been published. [7][8][9][10][11] Nevertheless, the applications of artificial intelligence and deep learning in this field are in the early stages. The broader capacity of deep learning to predict other systemic biomarkers based on retinal photographs, as well as the generalisation of the trained deep-learning algorithm, 12 remains unexplored.…”
Section: Introductionmentioning
confidence: 99%